KREATIVITAS GURU DALAM MEMANFAATKAN MEDIA PEMBELAJARAN UNTUK MENINGKATKAN ASPEK PERKEMBANGAN FISIK MOTORIK ANAK USIA 5-6 TAHUN DI PAUD PERMATA HATI DUSUN SANGE BARU TAHUN PELAJARAN 2021/2022 - Novia; Mujahidin; Hadisa Putri (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
This research aims to describe and analyze: 1) How creative teachers are in using learning media to improve aspects of children's physical motor development at PAUD Permata Hati; 2) What are the forms of teacher creativity in utilizing learning media; 3) What obstacles/constraints do teachers face in utilizing learning media to improve aspects of physical motor development? This research uses a qualitative approach with phenomenological research, data collection techniques using interviews, observation and documentation. The data analysis techniques used are data reduction, data display and conclusions. The research results show that; 1. Teacher creativity in utilizing learning media, namely by planning, in preparing RPPH, media, and preparing materials, with implementation so that it is carried out effectively and efficiently, evaluation by carrying out continuous assessments. 2. Forms of teacher creativity in utilizing learning media, namely: fluency in generating ideas/problems regarding media by sharing with teachers from other schools, flexibility/flexibility by utilizing the materials used to create learning media by utilizing used materials, originality in creating new and unique media and teacher skills in increasing children's enthusiasm for learning in the classroom so that children are active when delivering learning material 3. Barriers/constraints faced by teachers in utilizing learning media to improve aspects of physical motor development children aged 5-6 years at PAUD Permata Hati Dusun Sange Bakau, namely: lack of funds to buy media, the facilities provided by the school are inadequate, and teachers must be able to condition students.